Morphometric analysis of Desmodium Desv. in Bangladesh (Bangladesh Journal of Botany, 2013)
Phenetic analysis based on morphological characters is presented for 14 species of Desmodium Desv. in Bangladesh. This study examines patterns of morphological similarity and variation within Desmodium using 36 floral and vegetative characters. D. heterophyllum shows highest similarity with D. triflorum among the species employed. UPGMA dendrogram is constructed based on cluster analysis which reveals two major clusters, the first of which consists of seven species while the second cluster comprises six species, and D. microphyllum is found far from all other species. The presence of winged petioles distinguishes D. alatum and D. auriculatum from the other species. The present study shows the application of morphometric analysis for understanding the phenetic relationships among the species of Desmodium. DOI: http://dx.doi.org/10.3329/bjb.v41i2.13438 Bangladesh J. Bot. 41(2): 143-148, 2012 (December)